A Cross-Cultural Study on the Role of Message Framing in the Promotion of Fair-Trade Buying Behavior - The Anh Phan; Pham Ngoc Quyen Nguyen; Ngoc Anh Pham; Nhan Phan (SAGE Open, 2023)
This cross-cultural study investigates the differential effects of message framing techniques in promoting fair-trade consumption between Eastern and Western cultures. A total of 414 Vietnamese participants from Vietnam and 342 American participants recruited through Amazon Mechanical Turk were randomly assigned to two message framing conditions. It emphasizes the interconnected nature of fair-trade consumption behavior, influenced by message framing, processing fluency, and justice restoration effectiveness. The findings provide practical insights for marketers in effectively engaging consumers in purchasing fair-trade products. This study contributes to the literature by illuminating the impact of message framing strategies on consumer behavior toward fair-trade products in different cultural contexts. Marketers can leverage cultural orientations and message processing styles to develop more effective communication strategies for promoting fair-trade product adoption. Specifically, loss-framed messages may be more persuasive in increasing purchase intention among Vietnamese consumers, while gain-framed messages may resonate better with American consumers. Additionally, messages emphasizing the positive outcomes and benefits of fair-trade products for farmers and producers can enhance consumers’ likelihood of purchasing such products.